2013
DOI: 10.1159/000355213
|View full text |Cite
|
Sign up to set email alerts
|

A High Incidence of Adjacent-1 Meiotic Segregation Pattern, Revealed by Multicolor Sperm FISH, in a Carrier Boar of a New Reciprocal Translocation t(6;16)(p13;q23)

Abstract: Reciprocal translocations pose a serious problem in pig breeding due to the reduced fertility of the carriers. This paper presents a new reciprocal translocation in a phenotypically normal, but hypoprolific (20% reduction) boar. Chromosome banding as well as the FISH technique with the use of BAC and telomeric probes was applied for a detailed characterization of this chromosome rearrangement. The karyotype of the studied boar was described as 38,XY,t(6;16)(p13;q23). The meiotic segregation of the quadrivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Sperm meiotic segregation studies performed in human carriers of balanced reciprocal translocations showed that 18.6–80.7 % of the spermatozoa were chromosomally unbalanced (Benet et al 2005; Morel et al 2004). Until now, sperm FISH meiotic segregation analyses for three reciprocal translocations have only been carried out in pigs (Kociucka et al 2014; Massip et al 2008; Pinton et al 2004). One of these translocations (t(3;15)) was characterized by a small derivative chromosome (comparable in size to the der(14) chromosome observed in the present study) and a high proportion of 3:1 meiotic products (Pinton et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm meiotic segregation studies performed in human carriers of balanced reciprocal translocations showed that 18.6–80.7 % of the spermatozoa were chromosomally unbalanced (Benet et al 2005; Morel et al 2004). Until now, sperm FISH meiotic segregation analyses for three reciprocal translocations have only been carried out in pigs (Kociucka et al 2014; Massip et al 2008; Pinton et al 2004). One of these translocations (t(3;15)) was characterized by a small derivative chromosome (comparable in size to the der(14) chromosome observed in the present study) and a high proportion of 3:1 meiotic products (Pinton et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that in vitro fertilizing ability and percentage of sperm with damaged nuclear DNA seem not to change substantially over time in healthy sires (Hallap et al 2005;Foxcroft et al 2008). The same applies for RT disorders (Kociucka et al 2014). Therefore, single assessments performed when young healthy boars become part of AI-centres could be enough to obtain meaningful estimates of in vivo fertility potential expected throughout the productive life of an otherwise healthy boar.…”
Section: Boar Differences In Fertilitymentioning
confidence: 91%
“…The same applies for RT disorders (Kociucka et al. ). Therefore, single assessments performed when young healthy boars become part of AI‐centres could be enough to obtain meaningful estimates of in vivo fertility potential expected throughout the productive life of an otherwise healthy boar.…”
Section: Boar Differences In Fertilitymentioning
confidence: 98%
“…Similarly to centric fusions, decreased fertility is caused by the abnormal segregation of a tetravalent during anaphase I. However, the proportion of chromosomally unbalanced gametes is much higher in carriers of reciprocal translocations and varies between 20 and 50% [67]. As a consequence, a large proportion of the embryos die at an early embryonic stage, and thus the decrease of fertility is much more pronounced.…”
Section: Breed Description Of the Translocation Effect On Fertility Rmentioning
confidence: 99%
“…G-banded karyotype of a boar carrier of reciprocal translocation -t(6;16)(p13;q23). For details, see Kociucka et al[67].…”
mentioning
confidence: 99%